Technological Cybersecurity Strategies for the Digital Protection of Adolescents: A Systematic Review - Tacuri Gutierrez, Geovanna; Zatta Silva, Cesar Augusto (LACCEI, 2025)
The growing exposure of adolescents to digital risks—such as cyberbullying, loss of privacy, information manipulation, and contact with strangers—has prompted the development of specific technological strategies to protect them in virtual environments. This Systematic Literature Review (SLR) aims to identify, classify, and analyze cybersecurity strategies designed to safeguard adolescents, evaluating their characteristics, underlying technologies, effectiveness levels, and application contexts. Method: Following the PICOC framework and PRISMA guidelines, a systematic search was conducted in the Scopus database for articles published between 2020 and 2025. After applying inclusion and exclusion criteria, 30 relevant studies were selected and analyzed. Results: The strategies identified leveraged technologies such as artificial intelligence, automated parental control, educational gamification, and adaptive authentication systems. Conclusions: The most effective solutions combined pedagogical and technological approaches, emphasizing personalization, real‐time monitoring, and active engagement of both adolescents and responsible adults. Future research should adopt longitudinal designs with broader geographic diversity, and public policies should reinforce digital literacy and child safety in online environments